PEMANFAATAN PLATFORM KAHOOT SEBAGAI MEDIA GAME YANG INTERAKTIF PADA MATA PELAJARAN AQIDAH AKHLAK - Demina, Demina; Salma, Novita; Emryan, Noor Aisyah; Rahim, Refka (Universitas Islam Darul 'Ulum Lamongan, 2024)
Kahoot is an online-based application that can be used in the learning process. The use of the Kahoot platform as an interactive gaming media can be applied to moral aqidah subjects. Usually teachers explain learning material using the lecture method which tends to make learning monotonous and boring. In line with that, the aim of this research is that the Kahoot platform can provide interactive explanations and understanding in learning moral aqidah. By utilizing the game features on the Kahoot platform, it is hoped that learning aqidah and morals will become an interesting and enjoyable lesson. This research uses quantitative methods by distributing questionnaires online via WhatsApp. The results of this research are that students are able to use the game features on the Kahoot platform effectively and make the Kahoot platform an interactive game media on the subject of moral aqidah. The conclusion of this research can be explained that the Kahoot platform can optimize learning of moral aqidah in a fun way and can achieve the expected learning objectives. Due to the limitations of this research, the researcher only discussed the game features on the Kahoot platform. The researcher also hopes that future researchers can optimize all the features on the Kahoot platform in the subjects of aqidah, morals and other subjects.